Fungal and enzymatic pretreatments in hot-pressed lignocellulosic bio-composites: A critical review. (15th June 2022) - Sun, Wenjing; Tajvidi, Mehdi; Hunt, Christopher G.; Cole, Barbara J.W.; Howell, Caitlin; Gardner, Douglas J.; Wang, Jinwu
Abstract: Fungal and enzymatic pre-treatments have long been used to activate the surface of lignocellulosic biomass particles or fibers to promote adhesion or develop novel composite materials and other products. Research into mycelium-based bio-composites, i.e. products in which constituents are bonded by fungal mycelium, is quite new and still growing. There has also been a significant amount of attention given to these materials by the industry and private sector. These bio-composites can be produced by enzymatically or fungally treating lignoicellulosic substrates and then either molding them into a shape and letting the fungus grow or, alternatively, by hot-pressing the substrate into a panel product. This review article focuses on hot-pressed, higher density lignocellulosic bio-composites produced following enzymatic or fungal pretreatment. The definitions, raw materials, processing procedures, material properties, factors governing product properties, and potential adhesion mechanisms are summarized and discussed. Finally, current commercial products are introduced and roadblocks in the way of further development are presented along with the identification of knowledge gaps. Graphical abstract: Image 1 Highlights: Comprehensive review of fungal/enzymatic pretreatments of lignocellulosics. Critical review focused on pretreatments applied to hot-pressed bio-composites. Such pretreatments can enhance bonding by altering raw material properties. Roadblocks to industrial adoption are moisture resistance, process cost/efficiency.